The Impact of HIV/AIDS Criminalization on Awareness, Prevention and Stigma in the GTA - Chung, Karen; Greene, Brittany; Lax-Vanek, Jessica; Rans, Sofija; Shorkey, Allyson; Wilson, Michael (The Meducator, 2012)
In Canada, the exposure and/or transmission of HIV is punishable by criminal law. Deficiencies in Canadian-focused research about the implications of criminalizing HIV exposure demonstrate a need for locally applicable research evidence. This study aims to investigate the impact of HIV/AIDS criminalization on awareness, prevention, and stigma in the Greater Toronto Area through a scoping review and stakeholder interviews. Eleven databases were searched and the results were reviewed for relevance. Search yielded 1301 results, 148 relevant articles. Primary research is limited to 12 articles, while the remainder is comprised of case reports, editorials, commentaries and essays (n=136). Literature highlights confusion regarding behaviours constituting “significant risk”, resulting in dif- ficulties in the application of legal precedent and uncertainty regarding HIV knowledge in the general public. Some evidence suggests that criminalization contributes to disincentives for testing and disclosure, strained therapeutic relationships, HIV related stigma, and barriers to promoting shared responsibility for safer sex. Stakeholders (policy/content experts, executive directors and front-line workers from community-based HIV/AIDS organizations) were identified, and a purposive sample invited to participate in one-on-one, semistructured interviews. Interviews depict the negative impact of criminalization on prevention efforts, heightened community awareness of prosecutions, and increased stigmatization of people living with HIV/AIDS. Participants recommend guideline development to optimize the use of criminal law pertaining to HIV/AIDS non-disclosure. These findings will significantly contribute to increasing primary research on the impact of HIV/AIDS criminalization in the Greater Toronto Area. Further research is necessary to characterize the impact from the perspective of people living with HIV/AIDS.